Pre-analytical Practices in the Molecular Diagnostic Tests, A Concise Review - Maryam Anvari; Atoosa Gharib; Maryam Abolhasani; Aileen Azari-Yaam; Farzaneh Gharalari; Moeinadin Safavi; Ali Zare-Mirzaie; Mohammad Vasei (Iranian Society of Pathology, 2021)
Molecular assays for detection of nucleic acids in biologic specimens are valuable diagnostic tools supporting clinical diagnoses and therapeutic decisions. Pre-analytical errors, which occur before or during processing of nucleic acid extraction, contribute a significant role in common errors which take place in molecular laboratories. Certain practices in specimen collection, transportation, and storage can affect the integrity of nucleic acids before analysis. Applying best practices in these steps, helps to minimize those errors and leads to better decisions in patient diagnosis and treatment. Widely acceptable recommendations, which are for optimal molecular assays associated with pre-analytic variables, are limited. In this article, we have reviewed most of the important issues in sample handling from bed to bench before starting molecular tests, which can be used in diagnostic as well as research laboratories. We have addressed the most important pre-analytical points in performing molecular analysis in fixed and unfixed solid tissues, whole blood, serum, plasma, as well as most of the body fluids including urine, fecal and bronchial samples, as well as prenatal diagnosis samples.